Comparative Analysis of Reporting Bases of Czech Republic, Macedonia and Albania with IFRS: Are They Really So Different? - Strouhal, Jiří; Deari, Fitim (Asian Accounting and Auditing Advancement, 2013)
The European Union (EU) Regulation 1606/2002 requires all listed companies of the member states to prepare consolidated financial statements based on the International Financial Reporting Standards (IFRS) for accounting periods beginning on or after 1 January 2005. The adoption of IFRS is supported in many countries inside and outside the European Union because it may improve the quality and comparability of financial reporting. In addition to the use of IFRS by listed companies and in some countries also by unlisted companies, many countries have developed their own national accounting standards based on international ones. Although the national standards are based on IFRS, they are not identical. The Czech Republic, Macedonia, and Albania are transitional economies based in "Central and Eastern Europe". The Czech Republic joined the EU in May 2004, whereas Macedonia and Albania are still the candidate countries. The purpose of the paper is to compare national accounting standards of the Czech Republic, Macedonia, and Albania with IFRS, look at approaches of these countries to aspects of financial reporting, and analyze differences and similarities using Jaccard’s association coefficients as a general tool.